Deregulation as an Effort to Improve Public Services in Indonesia - Hutahaean, Marlan; Sinaga, Budiman; Sianturi, Widia Kartika Sari (PERSPEKTIF, 2024)
This article aims to understand various efforts to improve public services through deregulation. For example, the Mayor of Pekalongan shared complaints from fishermen who felt that the existence of the state and government made it difficult because to take care of sea permits alone had to deal with 17 different agencies. The problem centers on the obstacles to improving public services through deregulation and the factors that cause overregulation in Indonesia. This study determined the obstacles to public services and over-regulation. The data used are secondary data collected through literature studies and analyzed qualitatively. This study concludes that the Government has made various efforts to improve intermediate public services through deregulation by enacting several laws and regulations that unify the material of previous laws and regulations. Overregulation occurs in Indonesia due to the unclear development of authority between various institutions. There are still many overlapping laws and regulations in regulating various affairs so the applicable regulations can be said to have been too many. Therefore, there needs to be a firm policy in the division of authority of regulators so that there is no more over-regulation because there are no more overlapping regulations.